Sonographic analysis of speech sounds with varying positions of the upper anterior teeth - Ritchie, G.M.; Ariffin, Y.T. (Elsevier, 1982)
Sonographic analysis of speech sounds was used to investigate how setting the upper anterior teeth in positions different from those advocated affects the speech of denture-wearers and the adaptability of the tongue to alterations of intra-oral dimensions. From the findings, it can be concluded that the correct contour of the palate and positioning of anterior teeth are common requirements for the production of clear speech sounds, and changing intra-oral dimensions affects certain speech sounds to a varying degree. These sounds can be clear and intelligible again with time. The visual interpretation of spectrographs has given interesting results, confirmed by a panel which assessed the quality of the sounds.